Rheological properties of palm oil and palm-mineral oil blend - Wan Nik, Wan Sani; Ani, Farid Nasir; Hassan, Masjuki (Faculty of Mechanical Engineering, 2003)
This paper deals with the rheological study of refined bleached and deodorized grade palm oil, mineral oil and the effects of blending mineral oil with palm oil. This rheological study precedes the work done to investigate how hydraulic system performance and its dimensionless parameters are affected by palm oil properties. The aim of this initial work is to provide an equation to predict the apparent viscosity of the oils with better accuracy as a function of temperature and shear rates. The apparent viscosity of pure Shell Tellus 100, pure refined bleached and deodorized palm and their blends were measured over a temperature range of 30-100Â°C and shear rate range of 3.9-131.6s-1. It was observed that all oil samples viscosities were affected by shear rate and temperature. Therefore, a modified Andrade's equation was proposed. Viscosity data were fitted to the modified Andrade's equation for constant shear rate range of 3.9-131.6s-'. It was found that the modified Andrade's equation fits well with the experimental data where all the coefficient of determinations (R2) were greater than 0.98000.